Application of the Heck Reaction for the Synthesis of C-Glycosyl Phenolic Compounds - Tomé, Sara M.; Soengas, Raquel G.; Silva, Artur M. S. (Synthesis, 2023)
The potential of the Heck reaction for the C-glycosylation of phenolic compounds was explored. An efficient and general methodology for the synthesis of C-glycosylated phenolic compounds based on the Heck coupling of halogenated phenolic derivatives (chromones, 2-styrylchromones, and xanthones) and sugar alkenes was developed. The protocol was applied to the preparation of previously unreported C-glycosylated 2-styrylchromones and xanthones of potential biological relevance.
Keywords: Heck reaction; phenolic compounds; chromones; xanthones; 2-styrylchromones; C-glycosylation